Genome-wide analysis of alternative splicing differences in hepatic ischemia reperfusion injury - Yongliang Hua; Xinglong Li; Bing Yin; Shounan Lu; Baolin Qian; Yongzhi Zhou; Zhongyu Li; Zhanzhi Meng; Yong Ma (Scientific Reports)
Abstract Alternative splicing (AS) contributes to transcript and protein diversity, affecting their structure and function. However, the specific transcriptional regulatory mechanisms underlying AS in the context of hepatic ischemia reperfusion (IR) injury in mice have not been extensively characterized. In this study, we investigated differentially alternatively spliced (DAS) genes and differentially expressed transcripts (DETs) in a mouse model of hepatic IR injury using the high throughput RNA sequencing (RNA-seq) analysis and replicate multivariate analysis of transcript splicing (rMATS) analysis. We further conducted Gene ontology (GO) term enrichment, the Kyoto Encyclopedia of Genes and Genomes (KEGG) database and the protein-protein interaction (PPI) network. A total of 898 DAS genes (p ≤ 0.05) were screened out in the hepatic IR group compared to the sham group, while functional enrichment analysis revealed that DETs and DAS genes were significantly associated with the ATP-dependent chromain, splicesome and metabolic pathways. The expression level of the DAS genes: Gabpb2, Smg1, Tnrc6c, Mettl17, Smpd4, Kcnt2, D16Ertd472e, Rab3gap2, Echdc2 and Ssx2ip were verified by RT-PCR and qRT-PCR. Our findings provide a comprehensive genome-wide view of AS events in hepatic IR injury in mice, enhancing our understanding of AS dynamics and the molecular mechanisms governing alternative pre-mRNA splicing.